Importance of fluvial inflows in the intra-lake heterogeneity of surface water temperatures on the Tibetan Plateau - Bingqing Du; Jing Zhou; Deliang Chen; Hu Liu; Baoyan Liu; Ruishun Liu; Lei Wang (npj Climate and Atmospheric Science)
Abstract Lakes on the Tibetan Plateau (TP) are highly responsive to environmental change. Spatiotemporal variations in the lake surface water temperature (LSWT) significantly impact regional ecosystem stability, carbon cycling, and regional climate. However, due to limited observations, the intra-lake heterogeneity of LSWT and its driving forces remain unclear. By employing multi-source datasets, especially observation-constrained LSWT and lake inflow data, along with the random forest method, we analyzed three TP lakes (Nam Co, Siling Co, and Paiku Co) during 2001‒2019. No evident inter-annual LSWT changes were detected. Lake inflow (up to 40% contribution) was the main driver of LSWT variations from July to November, followed by air temperature. Spatially, LSWT intra-lake heterogeneity varied among lakes, with Siling Co showing the largest difference (nearly 4 °C) in autumn, mainly caused by river inflow locations and lake bathymetry. This study improves our understanding of the spatiotemporal variations of LWST for high-mountain lakes, providing insights for climate-change adaptation and water resources management.